1998
DOI: 10.1111/j.1399-6576.1998.tb05348.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenaline markedly improves thoracic epidural analgesia produced by a low‐dose infusion of bupivacaine, fentanyl and adrenaline after major surgery: A randomised, double‐blind, cross‐over study with and without adrenaline

Abstract: Adrenaline increases sensory block and improves the pain-relieving effect of a mixture of bupivacaine and fentanyl infused epidurally at a thoracic level after major thoracic or abdominal surgery. Serum fentanyl concentrations doubled and sedation increased when adrenaline was removed from the epidural infusion, indicating more rapid vascular absorption and systemic effects of fentanyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
1
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 43 publications
5
95
1
3
Order By: Relevance
“…Tem-se utilizado fentanil, ou morfina, associados aos anestésicos locais, por via peridural em dose única ou através de cateter, em doses intermitentes ou contínuas por bomba de infusão programada 8 . Estas bombas permitem o controle da analgesia pelo paciente, trazendo mais conforto e segurança, possibilitando uma maior interatividade do doente com sua recuperação [8][9][10][11][12][13][14] . Outra utilização destas bombas se faz por via venosa, porém com maior consumo de opióides 5,6 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Tem-se utilizado fentanil, ou morfina, associados aos anestésicos locais, por via peridural em dose única ou através de cateter, em doses intermitentes ou contínuas por bomba de infusão programada 8 . Estas bombas permitem o controle da analgesia pelo paciente, trazendo mais conforto e segurança, possibilitando uma maior interatividade do doente com sua recuperação [8][9][10][11][12][13][14] . Outra utilização destas bombas se faz por via venosa, porém com maior consumo de opióides 5,6 .…”
Section: Introductionunclassified
“…Epidural fentanyl or morphine associated to local anesthetics have been used in single doses or through catheter's, in intermittent boluses or continuous infusion by programmed infusion pump's 8 . These pumps allow analgesia to be patient-controlled, not only bringing more comfort and safety but also creating a higher interactivity of patients with their recovery [8][9][10][11][12][13][14] . There are pumps designed for intravenous infusion of drugs too, though its use is related to higher opioid consumption 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…In the United Kingdom, the epidural mixture typically consists of bupivacaine with either fentanyl or diamorphine in varying concentrations; other additives are unusual [1]. However, there is now increasing evidence that adding epinephrine to thoracic epidural infusions of bupivacaine and fentanyl produces superior postoperative analgesia with fewer side-effects [2][3][4][5]. A recent dose-finding study concluded that the minimally effective concentration of epinephrine to maintain postoperative pain relief is 1.5 lg.ml )1 when added to bupivacaine 1 mg.ml )1 and fentanyl 2 lg.ml )1 [6].…”
mentioning
confidence: 99%
“…The addition of adrenaline to continuous infusion techniques using local anesthetic-opioid mixtures led to reductions in drug consumption of approximately 25%. 10,17,18 It is possible that a 25% reduction in drug consumption from adrenaline was overshadowed by the observed five-fold variability in patient opioid requirements. A second consideration may be that satisfactory analgesia was obtained from the continuous epidural infusions used in both groups thereby limiting adrenaline's "treatment effect."…”
Section: Discussionmentioning
confidence: 99%
“…Both the consumption 10 and systemic levels of epidurally administered local anesthetics 11 and fentanyl 12 are reduced by the addition of adrenaline to the analgesic solution. To date there has been no trial evaluating the addition of adrenaline to meperidine for thoracic epidural analgesia.…”
Section: Conclusion : L'ajout D'adrénaline N'a Pas Influencé La Consomentioning
confidence: 99%